Persepsi Kualitas Produk, Electronic Word of Mouth, dan Citra Merek: Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian - Hasnah Rimiyati; Alfando Digo Sewanto (Penerbit Jurnal Indonesia, 2026)
This study aims to analyze the influence of Product Quality Perception and Electronic Word of Mouth on Purchase Decisions with Brand Image as a mediating variable in Nike shoe consumers in the Special Region of Yogyakarta. This study uses a quantitative approach with a survey method. The sample in this study was 202 respondents who were selected using the purposive sampling technique, namely consumers who had bought and used Nike brand shoes. Data collection was carried out through the distribution of questionnaires online and offline using Likert scale measurements. The data was analyzed using the Structural Equation Modeling method based on Partial Least Square (SEM-PLS). The results of the study show that Product Quality Perception has a positive and significant effect on Brand Image and Purchase Decisions. In addition, Electronic Word of Mouth also has a positive effect on Brand Image and Purchase Decisions. Brand Image has been proven to mediate the relationship between Product Quality Perception and Electronic Word of Mouth on Purchase Decisions. These findings indicate that the higher the perception of Electronic Word of Mouth quality and activity, the stronger the Nike brand image in the eyes of consumers, which ultimately drives increased purchasing decisions. The novelty of this research lies in the integration of Product Quality Perception and Electronic Word of Mouth in one empirical model with Brand Image as a mediating variable to explain consumer purchasing decisions which have been relatively limited in research.